2017
DOI: 10.1007/s13346-017-0379-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanistically elucidating the in vitro safety and efficacy of a novel doxorubicin derivative

Abstract: Doxorubicin is an effective anticancer drug; however, it is cardiotoxic and has poor oral bioavazilability. Quercetin is a plant-based flavonoid with inhibitory effects on P-glycoprotein (P-gp) and CYP3A4 and also antioxidant properties. To mitigate these therapeutic barriers, DoxQ, a novel derivative of doxorubicin, was synthesized by conjugating quercetin to doxorubicin. The purpose of this study is to mechanistically elucidate the in vitro safety and efficacy of DoxQ. Drug release in vitro and cellular upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
1
12
1
Order By: Relevance
“…DoxQ was synthesized by conjugating Dox to quercetin via a glycine linker, as previously described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DoxQ was synthesized by conjugating Dox to quercetin via a glycine linker, as previously described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, Dox is only currently available as a parenteral treatment administered intravenously. We have previously reported the synthesis of a Dox-quercetin derivative designed to overcome P–gp efflux and CYP inhibition [ 14 ] as quercetin is a natural flavonoid that exhibits inhibitory effects on CYP3A4 and P–gp [ 15 ] and an antioxidant that scavenges free radicals. Our in vitro investigation of DoxQ [ 14 ] revealed that both Dox and quercetin are released from the conjugate over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it was demonstrated that this conjugate inhibits CYP3 A4 and induces higher cellular uptake by P‐gp‐positive cells than doxorubicin only, despite the cleavage of the combined structure over time, leading to free quercetin and doxorubicin. There is also evidence to support the antitumoral activity and overall tolerability of doxorubicin‐quercetin complex, as observed in a triple‐negative murine breast cancer cell line, and decreased cardiotoxicity and renal side effects due to the inhibition of oxidative stress and CYP1B1, besides ROS scavenging property …”
Section: Anthracyclinesmentioning
confidence: 83%